2018
DOI: 10.1111/obr.12661
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota in obesity: interactions with enteroendocrine, immune and central nervous systems

Abstract: Western diets, with high consumption of simple sugars and saturated fats, contribute to the rise in the prevalence of obesity. It now seems clear that high-fat diets cause obesity, at least in part, by modifying the composition and function of the microorganisms that colonize in the gastrointestinal tract, the microbiota. The exact pathways by which intestinal microbiota contribute to obesity remain largely unknown. High-fat diet-induced alterations in intestinal microbiota have been suggested to increase ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 193 publications
2
69
1
1
Order By: Relevance
“…However, it is controversial whether HFD can reduce the level of SCFAs. It is reported that HFD increased the content of acetic acid, which is contrary to the results of other studies . The observed results highlighted that the production of SCFAs was inextricably linked to gut microbiota, and high fibre diet may have certain preventive effect on the occurrence of CRC …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, it is controversial whether HFD can reduce the level of SCFAs. It is reported that HFD increased the content of acetic acid, which is contrary to the results of other studies . The observed results highlighted that the production of SCFAs was inextricably linked to gut microbiota, and high fibre diet may have certain preventive effect on the occurrence of CRC …”
Section: Discussioncontrasting
confidence: 75%
“…It is reported that HFD increased the content of acetic acid, 49 which is contrary to the results of other studies. 13,50,51 The observed results highlighted that the production of SCFAs was inextricably linked to gut microbiota, and high fibre diet may have certain preventive effect on the occurrence of CRC. 47 Chemokines are structurally divided into CC, CXC, CX3C and C chemokines, and are well known for the ability to induce migration or chemotaxis of immune cells and involved in the pathogenesis cancers.…”
Section: Discussionmentioning
confidence: 85%
“…Obesity is a chronic disease characterized by long-term metabolic disorders and increases the risk of other diseases [1]. Microbiota-derived BA decreases the weights of mice with HFD induced obesity by weakening the activity of epithelial HDAC3 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have been compared to prebiotics, since by definition prebiotics are non-digestible polysaccharides. After metabolism by gut microbiota, these polysaccharides modulate the composition and/or function of the microbiota, providing a beneficial physiological effect on the host (14,91). Polyphenols may protect against diet-induced obesity, although their effects on food intake are controversial.…”
Section: Effects Of Phenolic-gut Microbiota Interactions On Obesity Amentioning
confidence: 99%
“…Polyphenols may protect against diet-induced obesity, although their effects on food intake are controversial. Possibly, polyphenols increase the secretion of mucin and remove reactive oxygen species (ROS), creating a beneficial environment for the bloom of the anaerobic Akkermansia muciniphila, and ameliorating metabolic endotoxemia (91). Resveratrol exerts effects on intestinal barrier function and integrity.…”
Section: Effects Of Phenolic-gut Microbiota Interactions On Obesity Amentioning
confidence: 99%